Diversity and habitat preferences of butterflies in Gorumara National Park, West Bengal, India - RP, Das; GK, Saha; JK, De; AK, Sanyal (Journal of Research in Biology, 2012)
Gorumara National Park is located towards the foothills of Eastern Himalayas in northern part in the state of West Bengal. A systematic survey on diversity, abundance and habitat preferences of butterflies was carried out from October 2009 to January 2011 to explore the butterfly richness of the protected area. An amazing 170 species of butterflies belonging to 109 genera, 21 sub-families, and five families were recorded from different habitats. Nymphalidae and Lycaenidae are the dominant families with maximum species count of 54 and 50 respectively; they are followed by Hesperiidae (33), Pieridae (18) and Papilionidae (15). Among the listed butterflies, 69 species are habitat specific; whereas 101 species are habitat generalists. Species count reaches the peak during pre-monsoon (April-May) period. Post-monsoon (October-November) and monsoon (June-September) periods have moderate species diversity and winter (December to March) period has least diversity. The abundance of butterflies is related to better availability and access to the larval host plants and nectar plants. In general forests and grasslands offer a better combination of habitat to the butterflies.